Deep-Learning-Based Approach for Iraqi and Malaysian Vehicle License Plate Recognition - Habeeb D.; Noman F.; Alkahtani A.A.; Alsariera Y.A.; Alkawsi G.; Fazea Y.; Al-Jubari A.M. (Hindawi Limited, 2023)
Accidents; Deep learning; Deterioration; Optical character recognition; Atmospheric environment; Learning-based approach; Learning-based methods; Malaysia; Malaysians; Recognition systems; State-of-the-art methods; Vehicle license plate recognition; License plates (automobile); machine learning; traffic accident; Accidents, Traffic; Deep Learning; Machine Learning